Actinidin-induced hydrolysis of milk proteins: Effect on antigenicity. (1st May 2022) - Kaur, S.; Huppertz, T.; Vasiljevic, T.
Abstract: Actinidin was used to hydrolyse proteins in whey protein isolate (WPI) and milk protein concentrate (MPC) to reduce immunoreactivity of β-lactoglobulin (β-LG) and αs1 -casein (αs1 -CN). Samples were incubated at an enzyme to substrate ratio of 1:100 (5.21 units of actinidin activity g −1 of protein) at 10 or 60 °C for up to 31 or 5 h, respectively. Protein hydrolysis was determined by the degree of hydrolysis and SDS-PAGE. Antigenicity of hydrolysates was determined by β-LG and αs1 -CN antibody-binding capacity using enzyme-linked immunosorbent assay (ELISA) quantification kits. ELISA showed significant reduction of antigenicity of β-LG and αs1 -CN with higher degree of hydrolysis (DH) by actinidin. At 60 °C, hydrolysis for 5 h resulted in antigenicity reduction of ∼43% for β-LG and ∼48% for αs1 -CN in MPC and ∼54% for β-LG in WPI. Hydrolysis at 10 °C for 31 h also resulted in decrease in antigenicity in MPC for β-LG and αs1 -CN by ∼39 and 42% respectively, but only 14% for β-LG in WPI. Treatment with actinidin can reduce the antigenicity by modification of protein conformation and cleavage and masking of epitopes of β-LG and αs1 -CN. Highlights: Actinidin, a plant protease from kiwi fruit, assessed for minimizing antigenicity of milk proteins. Milk protein concentrate or whey protein isolate used as a substrate. Lowering of antigenicity related to extent of hydrolysis. Antigenicity of αs1-CN and β-Lg reduced in a time and temperature dependent manner.